(untitled) (Observatorio Económico, 2009)
When designing social programs, one of the main features we economists consider is the degree of targeting; that is, that social policies reach those they are meant to reach. To that end, we collect information on individuals (through the Ficha de Protección Social, Chile’s social protection questionnaire, for example) and construct vulnerability indices in order to identify those who need it most. Continue reading...